(−)-4-O-(4-O-β-D-glucopyranosylcaffeoyl) quinic acid exerts anti-tumour effects against uveal melanoma through PI3K/AKT pathway. (3rd April 2021) - Kang, Hao; Ling, Feng; Xin, Xiangyang; Ping, Li
Abstract: Purpose: Uveal melanoma is the most common primary intraocular tumour in adults. There is no standard adjuvant treatment to prevent metastasis and no effective therapy in the metastatic setting. (−)-4-O-(4-O-β-D-glucopyranosylcaffeoyl) quinic acid (QA) is a new compound isolated from the endophytic fungus Penicillium sp.FJ-1 of Avicennia marina, with potent activities to inhibit the PI3K. Our work further investigated effects of QA against uveal melanoma and explored its underlying mechanisms. Methods: MP65 cells were treated with QA at different concentrations. CCK-8 assay was used to detect effects of QA on cell viability. PI staining was used to detect cell cycle arrest. Tumour model was established by injecting MP65 cells into nude mice subcutaneously. Tumour-bearing mice were divided into three groups (5 mice per group). Mice were treated with QA (5 or 10 mg/kg) or saline by intraperitoneal injection five times per week. RT-qPCR and western blot were used to detect the expression of genes and proteins, respectively. Results: QA significantly inhibited the proliferation of uveal melanoma cells and induced the cell cycle arrest as well as autophagy. Moreover, QA treatment significantly slowed tumour growth of uveal melanoma, shown by decreased tumour volume and weight. Furthermore, QA treatment markedly decreased the protein expression of p-PI3K and p-AKT in tumour tissues. Conclusions: Our data provided scientific rationale to develop QA as a promising anti-tumour agent against uveal melanoma.